The Main Reasons For Deviations From The Norms Of Behavior Of Adolescents - Qarshiboeva Gulnoza Abduqodirovna; Turdieva Sevinch Akbar kizi (Open Academia, 2023)
the article reveals the main reasons for deviance from adolescent standards of behavior, in which factors that cause deviant behavior in adolescents, researchers cite heredity, social environment, education and retardation in an individual's social activity
Keywords: Deviant behavior; factor; researchers; heredity